Відповідальність як фактор формування професійної суб’єктності курсантів як майбутніх офіцерів поліції - Тюріна, В. О.; Tiurina, V. O. (Адаптивне управління: теорія і практика. Серія "Педагогіка". - 2020. - Вип. 10(19), 2020)
Висвітлено значення сформованості професійної суб’єктності у курсантів як майбутніх офіцерів поліції для ефективного виконання службових обов’язків, особливо в екстремальних ситуаціях. Розкрито поняття «суб’єктність» і «професійна суб’єктність» офіцерів поліції, визначено якості особистості, які мають бути притаманні офіцеру поліції як фахівцю, у якого сформована професійна суб’єктність, і які визначають його ставлення до себе як суб’єкта спеціальної професійної діяльності, до своєї професії, до громадян, до результатів своєї діяльності. До числа таких якостей можна віднести ціннісну мотивацію діяльності, активність, відповідальність, самостійність, автономність, рефлексивність, усвідомлену модальність і варіативність, які характеризують здатність свідомо обирати засоби діяльності та цілеспрямовано детермінувати і регулювати власну поведінку, спілкування і діяльність у залежності від обставин. Зазначено, що професійна суб’єктність офіцера – це його інтегральна професійно значуща якість, яка, як і будь яка інша якість особистості, формується в процесі відповідної діяльності.

The article highlights the importance of the formation of professional subjectivity among cadets as future police officers for the effective performance of official duties, especially in extreme situations. The concepts of "subjectivity" and "professional subjectivity" of police officers are revealed, personality traits are determined, which should be inherent in a police officer as a specialist, who has formed a professional subjectivity, and which determine his attitude to himself as a subject of special professional activity, to his profession, to citizens, to the results of their activities. These qualities include the value motivation of activity, activity, responsibility, independence, autonomy, reflexivity, conscious modality and variability, which characterize the ability to consciously choose the means of activity and purposefully determine and regulate one's own behavior, communication and activity, depending on the circumstances. It is noted that the professional subjectivity of an officer is his integral professionally significant quality, which, like any other personality quality, is formed in the process of the corresponding activity. So, the subjectivity of the cadet is the result of his educational, cognitive and professional activities. It is also indicated that the period from 18 to 22 years is the age when the development of the subjective and professional qualities of a person occurs most intensively. Therefore, in higher education institutions, it is advisable to specifically create favorable conditions for the formation and manifestation of professional subjectivity as a professionally significant personality trait. This is evidenced by the results of the study, which showed that a special organization of the educational process, in particular, conducting trainings and practical classes with elements of training professional subjectivity contributes to an increase in the number of cadets who have a high level of subjective control. That is, the number of cadets has increased, in which the ability to take responsibility for their actions and the actions of subordinates has developed, which has a positive effect on professional subjectivity in general. Thus, the results of the study indicate that the special organization of the educational process in the institution of higher education contributes to the formation and development of the professional subjectivity of cadets as future police officers.

Освещено значение сформированности профессиональной субъектности у курсантов как будущих офицеров полиции для эффективного выполнения служебных обязанностей, особенно в экстремальных ситуациях. Раскрыты понятия «субъектность» и «профессиональная субъектность» офицеров полиции, определяются качества личности, присущие офицеру полиции как специалисту, у которого сформирована профессиональная субъектность, и которые определяют его отношение к себе как субъекта специальной профессиональной деятельности, к своей профессии, к гражданам, к результатам своей работы. К числу таких качеств можно отнести ценностную мотивацию деятельности, активность, ответственность, самостоятельность, автономность, рефлексивность, осознанную модальность и вариативность, которые характеризуют способность сознательно выбирать средства деятельности, целенаправленно детерминировать и регулировать собственное поведение, общение и деятельность в зависимости от обстоятельств. Отмечено, что профессиональная субъектность офицера это его интегральная профессионально значимое качество, которое, как и любое другое качество личности, формируется в процессе соответствующей деятельности.
Responsibility as a factor of forming the professional subject of coursants as future police officers
Ответственность как фактор формирования профессиональной субъектности курсантов как будущих офицеров полиции
Keywords: заклади вищої освіти; institutions of higher education; заведения высшего образования; майбутні офіцери поліції; future police officers; будущие офицеры полиции; суб’єктність; subjectivity; субъектность; відповідальність; responsibility; ответственность; професійна суб’єктність; professional subjectivity; профессиональная субъектность